2018
DOI: 10.1007/s40615-018-0517-7
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable Intake of US Hispanics by Food Store Type: Findings from NHANES

Abstract: This study examined fruit and vegetable intake by food store type shopped among US Hispanics. Using National Health and Nutrition Examination Survey 2011-2012 data, T test and chi-square tests examined differences between Hispanic consumers by food store type. Negative binomial regression analyses estimated associations between fruit and vegetable intake and food store type. Hispanics who only purchased fruits and vegetables from convenience stores were younger and more likely US born. They reported lower inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…The finding that the type of food outlet nearby influences eating is consistent with findings from previous literature [ 32 , 33 ] and is likely to be evidence that food outlet density is a proxy measure for the availability of food. For example, living within one mile of a grocery store has been associated with increased fruit and vegetable intake [ 18 ] and having numerous supermarkets in one’s neighborhood is associated with lower BMI [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…The finding that the type of food outlet nearby influences eating is consistent with findings from previous literature [ 32 , 33 ] and is likely to be evidence that food outlet density is a proxy measure for the availability of food. For example, living within one mile of a grocery store has been associated with increased fruit and vegetable intake [ 18 ] and having numerous supermarkets in one’s neighborhood is associated with lower BMI [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, on average, US Hispanic adults do not consume the recommended amount of fruits and vegetables, which may have affected participation rates in the suggested fruit and vegetable activities. In comparison to the recommended amount of 1.5-2 cups of fruit and 2-3 cups of vegetables daily, US Hispanic adults on average consume 0.78 cups of fruit and 1.33 cups of vegetables daily [21].…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have indicated that African American and Hispanic populations face challenges in accessing stores with organic food, while others have reported the opposite. Additionally, some studies have focused more on the convenience of shopping rather than the proximity and distance of these stores (Kumar et al 2011;D'Angelo et al 2011;Di Noia et al 2016;Evans, Banks, Jennings, et al 2015;Sanchez-Flack et al 2019;Zenk, Schulz, Hollis-Neely, et al 2005).…”
Section: Discussionmentioning
confidence: 99%